Chemotherapy plus Ofatumumab at Standard or Mega dose in relapsed CLL (COSMIC) trial: study protocol for a phase II randomised controlled trial. Issue 1 (December 2016) - Howard, Dena; Munir, Talha; Hockaday, Anna; Rawstron, Andy; Collett, Laura; Oughton, Jamie; Allsup, David; Bloor, Adrian; Phillips, David; Hillmen, Peter
Abstract Background Chronic lymphocytic leukaemia (CLL) is the most common adult leukaemia. Combination immunochemotherapy such as fludarabine, cyclophosphamide and rituximab is the standard first line therapy in fit patients, but there is limited evidence regarding the optimal treatment of patients after relapse. Ofatumumab as monotherapy has been proven to be effective in the treatment of relapsed, refractory CLL, and as it is not myelotoxic, it is an ideal drug to combine with chemotherapy. However, the optimal dose of ofatumumab in this setting is not known. The Chemotherapy plus Ofatumumab at Standard or Mega dose in relapsed CLL (COSMIC) trial will assess the efficacy and safety of standard and high (mega) doses of ofatumumab combined with bendamustine or a combination of fludarabine and cyclophosphamide to determine which, if either, schedule should progress to a phase III trial. Methods/design COSMIC is a phase II, multi-centre, randomised, open, parallel group trial for patients with relapsed CLL who are not refractory to fludarabine-based chemotherapy. Participants will be randomised to receive either standard dose or mega dose ofatumumab. Both doses will be given in combination with either bendamustine or fludarabine and cyclophosphamide chemotherapy backbone. The primary objective is to assess the proportion of participants achieving a complete remission following therapy with the two treatment arms (mega versus standard), as assessed at 3 months post treatment. The treatment groups will be assessed independently to determine whether the level of response is acceptable in relation to pre-specified criteria. If both treatment groups show an acceptable level of response, selection criteria will be used to determine which to take forward to a confirmatory phase III trial. A key secondary objective is to assess the dynamics of minimal residual disease (MRD) levels in relapsed disease. Eighty-two participants are planned to be recruited from 18 research centres in the UK. Discussion Currently there is limited evidence regarding the optimal treatment of patients with relapsed or refractory CLL, and so suitable therapies are urgently needed. The COSMIC trial will identify whether ofatumumab given in combination with chemotherapy is safe and effective in this population, and will identify the optimal doses for further investigation. Trial registration ISRCTN51382468 . Registered on 21 September 2011.